KARAKTERISTIK TANAH SULFAT MASAM DAN PENGELOLAANNYA UNTUK LAHAN PERTANIAN - Ida Nursanti; Yuza Defitri (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Acid sulfate soils are quite abundant in Indonesia, and some have been used for agricultural land. The main problem with this soil is the presence of pyrite compounds (FeS2). The oxidation of these compounds causes the soil to become acidic, metals and bases dissolve so that the soil becomes poor and the life of aquatic biota affected by the drainage water is disturbed. The oxidized soil, if flooded again, causes an increase in ferrous iron ions and hydrogen sulfide which can poison plants, therefore management of acid sulfate soils needs to be carried out so that the soil has characteristics that can support plant growth. Some soil management actions that can be taken are controlling the activity of microorganisms in the oxidation and reduction processes of pyrite, providing amelioration materials and fertilization, land management and water management.